Tai Solarin and education for self-reliance: a philosophical discourse (2015)
Over the years, western education has been widely accepted by many African countries to design their respective educational policies. Philosophical thinkers like Socrates, Plato, Aristotle, John Locke, etc, have been major influences in their quest for good educational policies. Although, there may appear to be defects or deficiencies in the educational practices of these traditional educational systems however, the neglect of their own ideas which are peculiar and relevant to their societies have become the bone in the development of their educational systems. While nothing may be wrong with appropriating educational ideas from non-African cultural backgrounds, total rejection of their own models of education is uncalled for. This paper therefore examines the ideas of Dr. Taiwo Solarin on Education for Self-reliance as a way out of the educational doldrums these countries are plunged into which, among others, had resulted in unemployment particularly, in Nigeria. The paper notes that although Nigeria’s education is rooted in self-reliance as stated in the National Policy on Education, commitment however, is only at the level of policy articulation. Using philosophical and analytical methodology, the paper examines education for self-reliance and posits that the present educational policy styles the graduates ’ initiatives to apply their theoretical knowledge pragmatically. The paper explores the views on education which reflects African cultural experiences based on vocational and technical education. The paper affirms that Nigeria is blessed with great thinkers and in our match to educational greatness, the paper concludes by advocating for the integration of Tai Solarins educational idea into the National Policy on Education in order to tackle unemployment in Nigeria